Being civil - Matshoba, Zongezile Theophilus (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My collection of short stories delves into government and governance, democracy, citizenship, civil servants, poverty, corruption and nepotism. My stories draw on the traditions of gritty urban crime fiction uncovering crimes of violence, service delivery, vandalism and corruption. They explore themes of mental cruelty and greed, self- preservation and community in rural areas, farms, townships and cities characterized by wrenching contradictions and inequalities.,This epic dramatic poetic verse delves into government and school governance, labour unions, liberation struggle, parenting and a wide range of school perceptions. It interrogates the roles of parents, teachers, students, department of education officials and that of other stakeholders that make use of schools. Influenced by William Wellington Gqoba's 'A great debate on education: a Parable' wayback, it continues the education debate in the current post-democratic South Africa characterized by wrenching contradictions and inequalities.,This thesis is presented in two parts: English and isiXhosa.
Intlambo yokufel'amahashe
Keywords: Uncatalogued